МЕТОДОЛОГІЯ ДОСЛІДЖЕНЬ ПРОЦЕСІВ РЕСУРСОСПОЖИВАННЯ - Scherbak, L.M. (Institute of Engineering Thermophysics of NAS of Ukraine, 2020)
On the basis of the analysis and generalization of known results of scientific researches the new methodology of scientific researches in edition object - model - measure - experiment - result is offered. This methodology is considered on an example of difficult dynamic processes of resource consumption, such as electric, gas and heat enegry consumption. The description of each subject of researches on the offered methodology has given. Multidimensional mathematical models of resource consumption processes using indicator functions for limiting time intervals and bounded space areas are considered. Physical probabilistic measures for obtaining quantitative information of research results are briefly described. It is emphasized that when conducting theoretical research, simulation, and field experiments, appropriate information support is used using software environments (Matlab, Mathcad, Statistica, Anaconda etc.) and networks for distributed computing. The requirements for the formation of the research result and options for its use are given.